EVALUATION AND SIMULATION OF IR.H. DJUANDA RESERVOIR OPERATING SYSTEM WITH MATLAB - Nurkhaerani, Fatma
Water availability will decrease over time. Ir.H. Djuanda Reservoir has various functions namely the provision of water for raw water communities, industries, irrigation, hydropower, etc. ROPP of Ir.H. Djuanda is heavily influenced by Saguling and Cirata Reservoirs because it is a cascade reservoir system. The study was created to determine the needs of raw water, irrigation, and current and future hydropower, to evaluation and simulation the Operating Patterns of Ir.H. Djuanda Reservoirs. The calculation results show that the discharge data used from 1974 to 2018 was conducted a homogeneity test that resulted in inhomogeneous data and can be used. Then synthetic discharge prediction is made with the Thomas Fierring method producing synthetic data that has a statistical value like the historical data. By 2035, the average raw water needs reached 64.08 m3/s, irrigation water needs were 113.18 m3/s, industrial water needs were 36.36 m3/s and water needs for hydropower reached 144.16 m3/s. Based on the evaluation of Ir.H. Djuanda reservoir operating pattern plan in 2019, the actual water level condition (normal) in 2019 is still between the two conditions of the previously planned limit. The actual highest of head occurred in June at 106,184 m, this condition is still below the normal limit of the plan of 106.28 m. While the actual lowest of head occurred in January at 92.53 m, it is still above the normal limit under the plan of 90.06 m. ROPP simulation results in 2025, 2030 and 2035 show that the volume and storage of Ir. H. Djuanda reservoirs have always decreased until 2035.